DAMPAK PANDEMI COVID-19 TERHADAP PROGRAM KEGIATAN BADAN USAHA MILIK DESA (BUMDES) (STUDI KASUS DI BUMDES SUKA MAJU DESA SAKRA SELATAN KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR) - PUTU KARISMAWAN; WAHIDIN WAHIDIN (GANEC SWARA, 2021)
The Covid-19 Pandemic has destroyed, not only healty sector but also  the economic of the society. The objectives of this research are to know the impact of Covid-19 Pandemic to activities of the BUMDes and  the economic of the sosiety of south Sakra Villages of Sakra Municipal of East Lombok distri of West Nusa Tenggara Province.The result of the research with descriptive qualitative approach are BUMDes have support economc of the society during Pandemi Covid-19.Bussines activites of the BUMDes such as rolling loan, goat farming, mini tractor services and mollen machine services have encourage economic of the society such asgoat farming,  groceries, chiken broiler and many others activities. The Religy Leader (Clergy) in religious activities always remain their society to encourage BUMDes activities by fulfill loan duty.  The constraints are decreasing of purchasing power, decrease of funding from the government because of fund policy to alocates to cope the disease and experience of administrator of the BUMDes is also one of the contraint in developing bussines plan.